2019
DOI: 10.3892/mmr.2019.9896
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of target CNVs and SNVs of thalassemia by multiplex PCR and next‑generation sequencing

Abstract: Thalassemia is caused by complex mechanisms, including copy number variants (CNVs) and single nucleotide variants (SNVs). The CNV types of α-thalassemia are typically detected by gap-polymerase chain reaction (PCR). The SNV types are detected by Sanger sequencing. In the present study, a novel method was developed that simultaneously detects CNVs and SNVs by multiplex PCR and next-generation sequencing (NGS). To detect CNVs, 33 normal samples were used as a cluster of control values to build a baseline, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The majority of the CNVs are extremely rare and unique to the families in which they have been described. As more of such CNVs are identified with universal screening, there is a need for a comprehensive single methodology akin to next-generation sequencing that can fully characterise breakpoints and genomic recombination events in a single analytical process [32]. Many studies suggest that WGS can be used to accurately locate the breakpoints of large segment deletions/duplications [33].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the CNVs are extremely rare and unique to the families in which they have been described. As more of such CNVs are identified with universal screening, there is a need for a comprehensive single methodology akin to next-generation sequencing that can fully characterise breakpoints and genomic recombination events in a single analytical process [32]. Many studies suggest that WGS can be used to accurately locate the breakpoints of large segment deletions/duplications [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang et al ( 43 ) reported a robust and versatile NGS-based cffDNA allelic molecule counting system termed the cffDNA barcode enabled single molecule test, which was developed for the non-invasive prenatal diagnosis of β-thalassemia. However, these methods mainly aim to identify SNV-associated thalassemia and have not been applied to CNV-associated thalassemia ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…RT was subsequently performed on RNA samples (2 µg) using the PrimeScript™ RT reagent (Takara Bio, Inc., Otsu, Japan), following the manufacturer's protocol. cDNA (1 µl) mixed with Ssofast™ EvaGreen ® Supermix (Bio-Rad Laboratories, Inc., Hercules, CA, USA), DEPC-treated water, forward primer and reverse primer (Sangon Biotech Co., Ltd.) to obtain a 20-µl reaction mixture was used for qPCR (22). qPCR was conducted as follows: 95°C for 30 sec, then 40 cycles of 95°C for 5 sec and 60°C for 30 sec.…”
Section: Methodsmentioning
confidence: 99%